The Effect of The Implementation of Cultural Implementation on Student Learning Motivation at Mts N 2 Cirebon City - Rodhotul Janah (Green Publisher Indonesia, 2021)
Cultural activities indirectly teach students to dare to appear in public, so that when in the community they are accustomed to speaking in public with their lectures. The purpose of this study was to determine the implementation of cultural habituation at MTs N 2 Cirebon City, to find out how much student motivation in MTs N 2 Cirebon City and how much influence the implementation of cultural habituation on student learning motivation. This research is quantitative. Held at MTs N 2 Cirebon City Jl. Kedung Menjangan Kalijaga, Harjamukti District, Cirebon City. Researchers took a sample of 32 students from a total population of 256 students to facilitate data collection in the field. The results of this research are the cult activities at MTs N 2 Cirebon City since 1982 until now these activities are still running. With cult activities, students can be motivated in learning, because the content in cult activities is not only about religion but also leads to learning motivation. Based on the research data obtained through the test with SPSS, the two variables in the study have a significant value (Sig.) Of 0.001 smaller than the 0.05 probability, so it can be concluded that H0 is rejected and Ha is accepted, which means that there is an influence of habituation. cult of student learning motivation at MTs N 2 Cirebon..